Investigation of Mechanical Properties of Aramid Fiber Reinforced HDPE Composite - Bekem, A.; Dogu, M.; Gemici, Z.; Unal, A. (DESTECH PUBLICATIONS, INC, 2013)
Aramid fiber has a wide application in several industries own to its extremely high mechanical and physical properties. High density polyethylene (HDPE) seems to be an inappropriate matrix alternative, because it is highly inert and hard to form a fiber-matrix interface. However, this property is unique in such application as liquid and gas storage or transportation. This study investigates production of an effective continuous aramid fiber reinforced HDPE composite. In order to improve fiber-matrix adhesion, maleic anhydride grafted polyethylene and ethylene-methyl acrylateglycidyl methacrylate terpolymer compatibilizers were applied as a tie-layer between matrix and fiber layers. Composite productions with compatibilizers were carried out on a laboratory scale press at 220 degrees C and 3 minutes. Adhesive lap-shear bond strengths of obtained composites with/ without tie layer were measured using the lap-shear tests. Tensile test were also applied to samples produced. Tensile strength values were compared with the lap-shear strength values. Mechanical test results were supported with SEM observations taken from the possible fiber-matrix interface regions and failure patterns observed on samples. Finally, it was found that both test results had same trends showing compatibilizer applications as tie-layer had improved the strength of HDPE composite.
Keywords: Aramid fiber; compatibilizer; HDPE; lap-shear test; tensile test; THERMOPLASTIC COMPOSITES; CORONA DISCHARGE; CARBON-FIBER; PERFORMANCE; Materials Science